Two Fragments of Early Dynastic Flint Bangles from Tell El-Murra in the Context of Finds from Ancient Egypt - Katarzyna Lajs (Studies in Ancient Art and Civilization, 2021)
The aim of this study is to present two fragments of flint bangles discovered in the remains of the settlement excavated at the site of Tell el-Murra (north-eastern Nile Delta). This group of artefacts, related to the Proto- and Early Dynastic periods, is known from several sites of Ancient Egypt, but their total number is still modest. The items from Tell el-Murra may contribute to the discussion on the method of production and distribution of this type of items.